2021
DOI: 10.1039/d0nr08369k
|View full text |Cite
|
Sign up to set email alerts
|

Promoting CO2 electroreduction on CuO nanowires with a hydrophobic Nafion overlayer

Abstract: A hydrophobic electrode surface was constructed by modifying the CuO nanowire electrode with a thick Nafion overlayer, which exhibited enhanced selectivity toward the CO2 electroreduction reaction and suppressed hydrogen evolution activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Chronoamperometric curves recorded during the electrolytic experiments are shown in Figure S12, and the integrated charge densities are plotted in Figure S13. It can be observed that the bare substrate and the no catalyst-modified electrode show similar small charge densities at −0.75 and −0.8 V due to the slow reaction rates, while at a more negative applied potential, the charge density of the no catalyst-modified electrode increases significantly compared to that of the bare substrate, which may be attributed to the higher local concentration of AN caused by the hydrophobic Nafion coating . In the presence of the MOF-derived electrocatalysts in the thin films, the charge densities at −0.75 and −0.8 V can be remarkably increased, which indicates that the MOF-derived electrocatalysts can initiate the electrochemical reactions at a lower overpotential compared to the bare Pb electrode and the Nafion-modified electrode.…”
Section: Resultsmentioning
confidence: 95%
“…Chronoamperometric curves recorded during the electrolytic experiments are shown in Figure S12, and the integrated charge densities are plotted in Figure S13. It can be observed that the bare substrate and the no catalyst-modified electrode show similar small charge densities at −0.75 and −0.8 V due to the slow reaction rates, while at a more negative applied potential, the charge density of the no catalyst-modified electrode increases significantly compared to that of the bare substrate, which may be attributed to the higher local concentration of AN caused by the hydrophobic Nafion coating . In the presence of the MOF-derived electrocatalysts in the thin films, the charge densities at −0.75 and −0.8 V can be remarkably increased, which indicates that the MOF-derived electrocatalysts can initiate the electrochemical reactions at a lower overpotential compared to the bare Pb electrode and the Nafion-modified electrode.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies point to the hydrophobic alkyl groups of CTAB in the catalyst microenvironment increasing the ratio of CO 2 -to-water near the catalyst surface. 36,37 To confirm this to be the case in our reactor, we ran similar experiments with dodecyltrimethylammonium bromide (DTAB), a quaternary ammonium surfactant with a 12-carbon alkyl chain (the alkyl chains of CTAB contain 16 carbon atoms; Figure S10). The DTAB-doped solution yielded a lower i CO2RR (89 ± 5 mA cm −2 ) than the CTAB-doped solution (162 ± 10 mA cm −2 ), yet both surfactants yielded a similar distribution of CO2RR products (Figure S10).…”
mentioning
confidence: 75%
“…We also compared the performance of the Cu-FEP sample with the reported state-of-the-art Cu-based catalysts in H-cells [8,21,[33][34][35][36]22,[26][27][28][29][30][31][32] and flow cells [18,24,[37][38][39][40][41] (Figure 5d), in terms of the partial current density and the applied potential. It is clear that in both the H-cell and flow cell reactors, our Cu-FEP sample is among the best Cu-based catalysts documented in the literature, showcasing high C 2+ selectivity and current density at relatively low overpotentials.…”
Section: Co 2 Rr Performancementioning
confidence: 99%